Pythagorean Fuzzy HX-subgroups and Their Applications (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we introduce the notion of a pythagorean fuzzy HX-subgroup and a normal HX-subgroup. In addition, we prove various chracterisations for pythagorean fuzzy HX-subgroups and pythagorean normal HX-subgroups. Moreover, the notations of pythagorean fuzzy HX-subgroups homomorphisms and antihomomorphisms are introduced, and some related properties regarding the relationship between a pythagorean fuzzy set and its image are investigated. Characterisations of level pythagorean fuzzy HX-subgroups and normal HX-subgroups are proved. These results generalised some results regarding fuzzy HX-subgroups.
Keywords: Pythagorean fuzzy sets; Pythagorean fuzzy homomorphism; normal HX-subgroups